Resilience and distress among individuals with chronic health conditions during the initial wave of the COVID-19 pandemic - Timothy R. Elliott; Paul B. Perrin; Mark B. Powers; Daniel Duffeck; Ann Marie Warren (Journal of Affective Disorders Reports, 2024)
Background: Individuals with chronic health conditions (CHCs) have a higher risk for severe SARS-CoV-2 (COVID-19) infection and reported high rates of distress during the pandemic. However, research suggests individual characteristics distinguish those who are more likely to experience clinical levels of distress than others. We examined predicted differences in distress over time between individuals with CHCs who had resilient and non-resilient personality profiles. Methods: A national sample responded to an online survey that included the study measures. Individuals with CHCs (N = 649) provided complete data to an initial survey and a second administered three months later. Cluster analysis of personality traits identified resilient and non-resilient personality profiles. A longitudinal structural equation model tested an a priori model that specified the relationship of a resilient personality prototype to self-reported resilience, coping, depression and anxiety at both measurement occasions. Results: The final model explained 50.2 % of the variance in distress at Time 1 and 76.2 % at Time 2. A resilient personality prototype significantly predicted less distress at Time 1, and at both time points it predicted and operated through self-reported resilience and less disengaged coping to effect lower distress. Limitations: Sampling biases may limit the generalizability of the study, as the study was limited to self-report data provided by those who completed the study measures at both assessments. Conclusions: Individuals with CHCs who are particularly vulnerable to distress may have characteristics that contribute to a lower sense of confidence and rely on ineffective, disengaged coping behaviors that exacerbate their stress.